Academic trajectories analysis with a life-course approach: A case study in medical students - Damián Canales Sánchez; Tomás Bautista Godínez; J. Gerardo Moreno Salinas; Manuel García-Minjares; Melchor Sánchez-Mendiola (Cogent Education, 2022)
Graduation rates and students’ academic trajectories can be used to determine universities’ performance and their response to curricular change. Longitudinal follow-up of students’ academic performance offers “natural experiments” to explore the impact of modified curricula. The goal of this study was to propose a method for analyzing students’ academic trajectories and identify changes associated with a curricular reform. We analyzed students’ trajectories throughout the program in two curricula (1994 and 2010), at the National Autonomous University of Mexico (UNAM) Faculty of Medicine. Advancement of each student was calculated using the accumulated credits in a defined time period, and the percentage of students that completed the credits for each stage of the curriculum. The theoretical framework was the “life course” approach, applying concepts of trajectory, transition and state. R software and TraMineR algorithm were used for data analysis. Five student cohorts of the older curriculum were studied (1994, 1995, 1996, 2004 and 2005 classes), and two cohorts of the new curriculum (2011, 2012), a total population of 6829 students. Students in the newer curriculum had a faster, more timely and efficient advancement in academic pathways, than cohorts in the older one. There was a higher percentage of students with “regular” trajectory (without failed courses) in the newer curriculum. Regularity is a straightforward metric that allows identification of curricular associated changes. This method allows the identification of inflection points throughout students’ academic trajectories, and contrasts pre-post curricular change data.